COMPETENCY‐BASED EVALUATION: A PARADIGM CHANGE. Issue 2 (February 2016) - Klein, Dan
Abstract : Most training units fail to evaluate training effectiveness in terms of return on investment (ROI). In this article the argument is made that this is a result of using an inadequate evaluation paradigm. The author suggests a paradigm that is based upon a common cost‐benefit framework. As such, the alternative paradigm a) will be more understood and accepted by other managers in the organization, b) will enable the evaluation of the full scope of training activities all within one framework including effectiveness, cost, quality and efficiency‐related activities. In order to measure effectiveness we have to broaden the definition of the term performance improvement . The definition should relate also to the cost of behavioral change. In addition, we have to differentiate between evaluations of training effectiveness and consulting effectiveness. These two changes will enable us to link directly, training activities to performance improvement. Training results will improve human capital and could be measured in ROI terms.